Materiality of Mid-Century Modern Furniture in Turkey - Zeynep Tuna Ultav; Deniz Hasırcı; Hande Atmaca Çetin (Art-Sanat)
The modern interior emerged as a complex phenomenon, an interchange of modernity and its materiality. One of the constituent elements of this complexity is the progressive relationship with technology. This paper explores the materiality of furniture in terms of its material qualities, production technologies, craft component and inefficacies. The paper focuses on mid-century modern furniture in Turkey as a unique example in the history of furniture design, especially in terms of materiality. In order to understand the material qualities of this historical context, oral history provided a vital methodological tool to uncover the philosophy behind production, contemporary conditions and the designers’ personal experiences through their own words. This enables the study to add significantly to the limited knowledge about modern furniture and especially materials in Turkey. The analysis is divided into three parts: materials, production technologies and difficulties. By investigating the material qualities of a furniture piece, the study extends beyond mere forms or styles to cultural productions that narrate the country’s efforts to develop and thrive. In addition, it reveals the evolution of both materials and manufacturing techniques. Finally, by connecting these stories to specific furniture pieces, this study documents furniture not just as an artefact but also as the final product of an assemblage of people, materials, and techniques.